Functional structure and method for producing same
Patent Information
- Application Number
- JP2023197656
- Authority / Receiving Office
- JP · JP
- Patent Type
- Patents
- Current Assignee / Owner
- Filing Date
- 2023-11-21
- Publication Date
- 2025-02-26
- Estimated Expiration
- 2038-12-03
AI Technical Summary
【0012】 本発明によれば、機能性物質の微粒子同士の凝集を防ぐと共に、活性の低下を抑制して長寿命化を実現することができる機能性構造体及びその製造方法を提供することができる。
Smart Images

Figure 0007635945000005 
Figure 0007635945000006 
Figure 0007635945000007
Abstract
Description
[Technical field]
[0001] The present invention relates to a functional structure and a manufacturing method thereof. [Background technology]
[0002] As a method for producing hydrocarbon compounds used as raw materials for liquid fuel products such as synthetic oils and synthetic fuels, which are alternative fuels to petroleum, the Fischer-Tropsch synthesis reaction (hereinafter sometimes referred to as the "FT synthesis reaction") is known, which uses a catalytic reaction to synthesize hydrocarbons, particularly liquid hydrocarbons, from a synthesis gas mainly composed of carbon monoxide gas (CO) and hydrogen gas (H2). As a catalyst used in this FT synthesis reaction, for example, Patent Document 1 discloses a catalyst in which an active metal such as cobalt or iron is supported on a support such as silica or alumina, and Patent Document 2 discloses a catalyst containing cobalt, zirconium or titanium, and silica.
[0003] The catalyst used in the FT synthesis reaction can be obtained as a catalyst (unreduced catalyst) carrying cobalt oxide and / or ruthenium oxide by impregnating a carrier such as silica or alumina with a cobalt salt, a ruthenium salt, or the like, and then calcining the carrier. In order for the catalyst obtained in this manner to exhibit sufficient activity in the FT synthesis reaction, as disclosed in Patent Document 3, the catalyst must be brought into contact with a reducing gas such as hydrogen gas for reduction treatment, and the active metals, cobalt and / or ruthenium, must be converted from the oxide state to the metal state.
[0004] Incidentally, as disclosed in Patent Document 4, the FT synthesis reaction generates a large amount of heat, and it is known that the locally overheated spots on the catalyst surface become hot spots, and the progression of side reactions (such as carbonaceous precipitation) on the catalyst surface due to these hot spots reduces activity. In order to prevent the generation of such hot spots, it is necessary to disperse active points without agglomerating fine particles of active metal species (metal fine particles), which are functional substances that act as catalysts. In order to prevent the aggregation of fine particles of active metal species, it is possible to use a carrier that has a strong interaction with the active metal species, so that the metal fine particles cannot easily aggregate with each other.
[0005] One example of this method is the sol-gel method, which supports metal particles in a highly dispersed state. In the sol-gel method, active metal species are introduced uniformly at the atomic level during the synthesis of the metal oxide support. The active metal species of the supported metal catalyst are highly dispersed within the lattice of the metal oxide support, so they do not easily aggregate during various treatments or reactions. However, because the active metal species are strongly bound to the support, it is difficult to activate the catalyst prior to the reaction, which has led to the problem of insufficient catalytic activity being obtained.
[0006] In addition, when metal particles aggregate, the effective surface area of the catalyst decreases, and the catalytic activity decreases, so the life of the catalyst itself becomes shorter than usual. Therefore, the catalyst itself must be replaced or regenerated in a short period of time, which is troublesome and does not allow for resource conservation. In addition, there is a demand for the catalyst to maintain its catalytic activity for a long period of time.
[0007] The problem of decreased activity due to aggregation of fine particles is not limited to metal fine particles used as catalysts in the FT synthesis reaction, but also occurs in fine particles of other functional substances. Therefore, there is a demand for a functional structure that can hold fine particles of functional substances without agglomerating them. [Prior art documents] [Patent documents]
[0008] [Patent Document 1] Japanese Patent Application Publication No. 4-227847 [Patent Document 2] Japanese Patent Publication No. 59-102440 [Patent Document 3] International Publication No. 2015 / 072573 [Patent Document 4] JP 2000-70720 A Summary of the Invention [Problem to be solved by the invention]
[0009] An object of the present invention is to provide a functional structure capable of preventing aggregation of fine particles of a functional substance and suppressing a decrease in activity to realize a long life, and a method for producing the same. [Means for solving the problem]
[0010] As a result of intensive research into achieving the above-mentioned object, the inventors have discovered that a functional structure can be obtained which comprises a porous support composed of a zeolite-type compound and at least one functional substance contained within the support, the support having mutually communicating passages, the support containing aluminum and silicon, the Si / Al atomic ratio contained in the support being 2.0 or more, and the functional substance being present at least in the passages of the support, thereby preventing aggregation of fine particles of the functional substance, suppressing a decrease in activity, and realizing a longer life, and have completed the present invention based on this finding.
[0011] That is, the gist of the present invention is as follows. [1] A porous support composed of a zeolite-type compound, and at least one functional substance present in the support; Equipped with The support contains aluminum (Al) and silicon (Si); The atomic ratio (Si / Al ratio) of silicon (Si) to aluminum (Al) contained in the support is 2.0 or more; The carrier has passages communicating with each other, The functional material is present in at least the passages of the carrier. A functional structure characterized by: [2] The passage has one of one-dimensional pores, two-dimensional pores, and three-dimensional pores defined by the framework structure of the zeolite-type compound, and an expanded portion different from any of the one-dimensional pores, the two-dimensional pores, and the three-dimensional pores; and The functional structure according to [1] above, characterized in that the functional substance is present at least in the expanded diameter portion. [3] The functional structure according to [2] above, wherein the enlarged diameter portion connects a plurality of holes constituting any one of the one-dimensional hole, the two-dimensional hole, and the three-dimensional hole. [4] The functional structure according to [2] or [3] above, characterized in that the average particle size of the functional substance is larger than the average inner diameter of the passage and is equal to or smaller than the inner diameter of the expanded portion. [5] The functional structure according to any one of the above [1] to [4], characterized in that the metal element (M) of the functional substance is contained in an amount of 0.5 to 2.5 mass % relative to the functional structure. [6] The functional structure according to any one of the above [1] to [5], wherein the functional substance is metal oxide fine particles. [7] The functional structure according to any one of the above [1] to [5], wherein the functional substance is a metal fine particle. [8] The functional structure described in [7] above, characterized in that the metal microparticles contain one or more metals or alloys selected from the group consisting of cobalt (Co), iron (Fe), nickel (Ni) or ruthenium (Ru). [9] The functional structure according to any one of the above [1] to [8], wherein the average particle size of the functional substance is 0.08 nm to 30 nm.
[10] The functional structure according to any one of the above [1] to [9], characterized in that the ratio of the average particle size of the functional substance to the average inner diameter of the passages is 0.05 to 300.
[11] The functional structure according to any one of the above [1] to
[10] , wherein the average inner diameter of the passage is 0.1 nm to 1.5 nm.
[12] The functional structure according to any one of the above [2] to
[11] , wherein the inner diameter of the expanded portion is 0.5 nm to 50 nm.
[13] The functional structure according to any one of [1] to
[12] above, further comprising at least one other functional substance held on the outer surface of the carrier.
[14] The functional structure described in
[13] above, characterized in that the content of the at least one functional substance contained within the carrier is greater than the content of the at least one other functional substance held on the outer surface of the carrier.
[15] The functional structure according to any one of the above [1] to
[14] , wherein the zeolite type compound is a silicate compound.
[16] A hydrocarbon production device having the functional structure according to any one of the above [1] to
[15] .
[17] A calcination step of calcining a precursor material (B) obtained by impregnating a precursor material (A) with a metal-containing solution to obtain a porous support composed of a zeolite-type compound; a hydrothermal treatment step of subjecting the precursor material (C) obtained by calcining the precursor material (B) to a hydrothermal treatment; A method for producing a functional structure comprising the steps of: The precursor material (A) contains aluminum (Al) and silicon (Si); A method for producing a functional structure, comprising preparing the precursor material (A) so that the atomic ratio of silicon (Si) to aluminum (Al) (Si / Al ratio) is 2.0 or more.
[18] The method for producing a functional structure according to the above
[17] , characterized in that a nonionic surfactant is added in an amount of 50 to 500 mass % based on the precursor material (A) prior to the firing step.
[19] The method for producing a functional structure according to the above
[17] or
[18] , characterized in that, prior to the firing step, the metal-containing solution is added to the precursor material (A) in multiple batches, thereby impregnating the precursor material (A) with the metal-containing solution.
[20] The method for producing a functional structure according to any one of the above
[17] to
[19] , characterized in that, when impregnating the precursor material (A) with the metal-containing solution prior to the firing step, an amount of the metal-containing solution added to the precursor material (A) is adjusted so that an atomic ratio Si / M of silicon (Si) constituting the precursor material (A) to a metal element (M) contained in the metal-containing solution added to the precursor material (A) is 10 to 1000.
[21] The method for producing a functional structure according to any one of the above
[17] to
[20] , wherein in the hydrothermal treatment step, the precursor material (C) is mixed with a structure-directing agent.
[22] The method for producing a functional structure according to any one of the above
[17] to
[21] , wherein the hydrothermal treatment step is carried out in a basic atmosphere.
[23] A method for producing a Fischer-Tropsch synthesis catalyst structure according to any one of
[17] to
[22] above, further comprising a step of subjecting the hydrothermally treated precursor material (C) to a reduction treatment. Effect of the Invention
[0012] According to the present invention, it is possible to provide a functional structure and a manufacturing method thereof that can prevent aggregation of fine particles of a functional substance and also suppress a decrease in activity to realize a long life. [Brief description of the drawings]
[0013] [Figure 1] FIG. 1 is a schematic diagram showing the internal structure of a functional structure according to an embodiment of the present invention, with FIG. 1(a) being an oblique view (partially shown in cross section) and FIG. 1(b) being a partially enlarged cross-sectional view. [Diagram 2]FIG. 2 is a partially enlarged cross-sectional view for explaining the catalytic function, which is an example of the function of the functional structure in FIG. 1, where FIG. 2(a) is a diagram explaining the sieving function and FIG. 2(b) is a diagram explaining the catalytic ability. [Diagram 3] FIG. 3 is a flowchart showing an example of a method for manufacturing the functional structure of FIG. [Figure 4] FIG. 4 is a schematic diagram showing a modified example of the functional structure of FIG. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS
[0014] Hereinafter, an embodiment of the present invention will be described in detail with reference to the drawings.
[0015] [Configuration of functional structures] Fig. 1 is a diagram showing a schematic configuration of a functional structure according to an embodiment of the present invention, where (a) is a perspective view (partially shown in cross section), and (b) is a partially enlarged cross-sectional view. Note that the functional structure in Fig. 1 shows one example, and the shape, dimensions, etc. of each component according to the present invention are not limited to those in Fig. 1.
[0016] As shown in FIG. 1( a ), the functional structure 1 comprises a support 10 having a porous structure composed of a zeolite-type compound, and at least one functional substance 20 present within the support 10 .
[0017] The functional structure 1 is a substance that exerts one or more functions, at least during use, either alone or in cooperation with the support 10 or the like. Specific examples of the above functions include a catalytic function, a light emitting (or fluorescent) function, a light absorbing function, and a recognition function. The functional structure 1 is preferably, for example, a catalytic substance having a catalytic function. When the functional structure 1 is a catalytic substance, the support 10 is a support that supports the catalytic substance.
[0018] In the functional structure 1, a plurality of functional substances 20, 20, ... are encapsulated within the porous structure of the support 10. The functional substance 20 is a substance having functionality (e.g., catalytic activity when used as a catalyst) and has the form of fine particles. The functional substance will be described in detail later. The functional substance 20 may also be particles containing a metal, a metal oxide, a metal alloy, or a composite material thereof.
[0019] 1(b), the carrier 10 has a porous structure, and preferably has a plurality of pores 11a, 11a, ... formed therein to form mutually communicating passages 11. Here, the functional substance 20 is present in at least the passages 11 of the carrier 10, and is preferably held in at least the passages 11 of the carrier 10.
[0020] With this configuration, the movement of the functional material 20 within the support 10 is restricted, and the aggregation of the functional materials 20, 20 with each other is effectively prevented. As a result, the reduction in the effective surface area of the functional material 20 can be effectively suppressed, and the activity of the functional material 20 is maintained for a long period of time. In other words, according to the functional structure 1, the decrease in catalytic activity due to aggregation of the functional material 20 can be suppressed, and the life of the functional structure 1 can be extended. Furthermore, the extended life of the functional structure 1 can reduce the frequency of replacement of the functional structure 1, and the amount of waste of used functional structures 1 can be significantly reduced, thereby saving resources.
[0021] Usually, when a functional structure is used in a fluid (e.g., heavy oil or reformed gas such as NOx), it may be subjected to an external force from the fluid. In this case, if the functional substance is only held in an attached state on the outer surface of the carrier 10, there is a problem that the functional substance is easily detached from the outer surface of the carrier 10 due to the influence of the external force from the fluid. In contrast, in the functional structure 1, the functional substance 20 is present at least in the passage 11 of the carrier 10, so that the functional substance 20 is unlikely to be detached from the carrier 10 even if it is affected by the external force from the fluid. That is, when the functional structure 1 is in a fluid, the fluid flows into the passage 11 from the hole 11a of the carrier 10, so that the speed of the fluid flowing in the passage 11 is considered to be slower than the speed of the fluid flowing on the outer surface of the carrier 10 due to the flow path resistance (friction force). Due to the influence of such flow path resistance, the pressure that the functional substance 20 held in the passage 11 receives from the fluid is lower than the pressure that the functional substance receives from the fluid outside the carrier 10. Therefore, it is possible to effectively prevent the functional substance 20 contained in the carrier 10 from being released, and to stably maintain the activity of the functional substance 20 for a long period of time. It is considered that the above-mentioned flow path resistance becomes larger as the passage 11 of the carrier 10 has a plurality of bends and branches and the inside of the carrier 10 has a more complicated three-dimensional structure.
[0022] The carrier 10 is a zeolite-type compound containing aluminum (Al) and silicon (Si), and the atomic ratio (Si / Al ratio) of silicon (Si) to aluminum (Al) contained in the carrier 10 is 2.0 or more. By using a zeolite-type compound with a high proportion of silicon (Si) as the carrier 10, the production of zeolite-type crystals in the functional structure is increased, making it possible to produce a stronger zeolite-type compound, and therefore a more durable functional structure can be obtained. From this perspective, the Si / Al ratio in the carrier 10 is preferably 5.0 or more, more preferably 8.0 or more. On the other hand, the upper limit of the Si / Al ratio in the carrier 10 may be infinite (i.e., a trace amount of aluminum (Al) is contained), but it is preferable that the Si / Al ratio be less than 10 from the viewpoint of production efficiency, for example. 9The upper limit may be 10 6 The upper limit of the Si / Al ratio may be set to be less than 50, and from the viewpoint of improving the selectivity of the product, the Si / Al ratio is preferably set to less than 50.
[0023] In addition, the passage 11 preferably has one of one-dimensional pores, two-dimensional pores, and three-dimensional pores defined by the framework structure of the zeolite-type compound, and an expanded diameter portion 12 different from any of the one-dimensional pores, two-dimensional pores, and three-dimensional pores. In this case, the functional material 20 is preferably present at least in the expanded diameter portion 12, and more preferably is included in at least the expanded diameter portion 12. In addition, the expanded diameter portion 12 preferably communicates with a plurality of holes 11a, 11a constituting any of the one-dimensional pores, two-dimensional pores, and three-dimensional pores. This provides a separate passage different from the one-dimensional pores, two-dimensional pores, or three-dimensional pores inside the carrier 10, so that the function of the functional material 20 can be more effectively exhibited. The one-dimensional pores referred to here refer to tunnel-type or cage-type pores forming a one-dimensional channel, or multiple tunnel-type or cage-type pores (multiple one-dimensional channels) forming multiple one-dimensional channels. Furthermore, the term "two-dimensional pore" refers to a two-dimensional channel in which a plurality of one-dimensional channels are two-dimensionally connected, and the term "three-dimensional pore" refers to a three-dimensional channel in which a plurality of one-dimensional channels are three-dimensionally connected. This further restricts the movement of the functional substance 20 within the carrier 10, and more effectively prevents the functional substance 20 from being separated and the functional substances 20, 20 from aggregating with each other. "Inclusion" refers to a state in which the functional substance 20 is encapsulated in the carrier 10. In this case, the functional substance 20 and the carrier 10 do not necessarily need to be in direct contact with each other, and the functional substance 20 may be indirectly held by the carrier 10 with another substance (e.g., a surfactant, etc.) intervening between the functional substance 20 and the carrier 10.
[0024] 1(b) shows a case where the functional substance 20 is encapsulated in the enlarged diameter portion 12, but the present invention is not limited to this configuration, and the functional substance 20 may be held in the passage 11 with a part of it protruding outside the enlarged diameter portion 12. The functional substance 20 may also be partially embedded in a part of the passage 11 other than the enlarged diameter portion 12 (for example, an inner wall part of the passage 11) or held by adhesion or the like.
[0025] Moreover, the passage 11 is formed three-dimensionally inside the carrier 10 including a branching portion or a junction portion, and the expanded diameter portion 12 is preferably provided at the branching portion or the junction portion of the passage 11 .
[0026] The average inner diameter D of the passages 11 formed in the carrier 10 F is calculated from the average value of the minor axis and major axis of the pores 11a constituting any one of the one-dimensional pores, the two-dimensional pores, and the three-dimensional pores, and is, for example, 0.1 nm to 1.5 nm, and preferably 0.5 nm to 0.8 nm. E The inner diameter D of the expanded diameter portion 12 is, for example, 0.5 nm to 50 nm, preferably 1.1 nm to 40 nm, and more preferably 1.1 nm to 3.3 nm. E is, for example, the pore size of the precursor material (A) described later and the average particle size D of the functional material 20 to be enclosed. C The inner diameter D of the expanded diameter portion 12 depends on E is a size capable of encapsulating the functional substance 20.
[0027] The carrier 10 is composed of a zeolite-type compound. Examples of the zeolite-type compound include silicate compounds such as zeolite (aluminosilicate), cation-exchanged zeolite, and silicalite, zeolite-related compounds such as aluminoborates, aluminoarsenates, and germanates, and phosphate-based zeolite-like substances such as molybdenum phosphate. Among these, the zeolite-type compound is preferably a silicate compound, and more specifically, it is preferably zeolite or silicalite.
[0028] The framework structure of the zeolite compound is selected from FAU type (Y type or X type), MTW type, MFI type (ZSM-5), FER type (ferrierite), LTA type (A type), MWW type (MCM-22), MOR type (mordenite), LTL type (L type), BEA type (beta type), etc., preferably MFI type, MOR type, BEA type, more preferably MFI type. In the zeolite compound, a plurality of pores having a pore size according to each framework structure are formed, for example, the maximum pore size of the MFI type is 0.636 nm (6.36 Å) and the average pore size is 0.560 nm (5.60 Å).
[0029] The functional material 20 has a form of fine particles, and may be a primary particle or a secondary particle formed by aggregation of the primary particles. The average particle diameter D C is preferably the average inner diameter D of the passage 11 F and the inner diameter D of the expanded diameter portion 12 is larger than E The following is true: F <D C ≦D E ). Such functional material 20 is preferably present in the expanded diameter portion 12 in the passage 11, and the movement of the functional material 20 in the carrier 10 is restricted. Therefore, even if the functional material 20 is subjected to an external force from the fluid, the movement of the functional material 20 in the carrier 10 is restricted, and the functional materials 20, 20, ... present in the expanded diameter portions 12, 12, ... dispersedly arranged in the passage 11 of the carrier 10 can be effectively prevented from contacting each other.
[0030] In addition, the average particle diameter D of the fine particles of the functional material 20 C In both the case of the primary particles and the secondary particles, the average inner diameter D of the passages 11 is preferably 0.08 nm to 30 nm, more preferably 0.1 nm or more and less than 25 nm, further preferably 0.4 nm to 11.0 nm, and particularly preferably 0.8 nm to 2.7 nm. F Average particle size D of functional material 20 C Percentage of (D C / D F) is preferably 0.05 to 300, more preferably 0.1 to 30, even more preferably 1.1 to 30, and particularly preferably 1.4 to 3.6. The metal element (M) of the functional substance 20 is preferably contained in an amount of 0.5 to 2.5 mass% relative to the functional structure 1, and more preferably 0.5 to 1.5 mass% relative to the functional structure 1. For example, when the metal element (M) is Co, the content (mass%) of the Co element is expressed by {(mass of Co element) / (mass of all elements in the functional structure 1)}×100.
[0031] The functional substance may include metals consisting of one metal element, mixtures of two or more metal elements, or metal particles in which at least a part of them are alloyed. The functional substance 20 may also include metal oxide particles consisting of oxides of one or more metal elements or composite materials thereof. In this specification, the term "metal" (as a material) constituting the functional substance includes simple metals containing one metal element (M) and metal alloys containing two or more metal elements (M), and is a general term for metals containing one or more metal elements.
[0032] Examples of metal elements contained in metal fine particles and metal oxide fine particles include platinum (Pt), palladium (Pd), ruthenium (Ru), nickel (Ni), cobalt (Co), molybdenum (Mo), tungsten (W), iron (Fe), chromium (Cr), cerium (Ce), copper (Cu), magnesium (Mg), and aluminum (Al). It is preferable that the main component is one or more of the above, more preferably cobalt, iron, nickel, or ruthenium, even more preferably cobalt, iron, or nickel, and particularly preferably cobalt. In particular, it is preferable that the metal fine particles contain one or more metals or alloys selected from the group consisting of cobalt, iron, nickel, and ruthenium. It is also preferable that the metal oxide fine particles contain one or more metal elements selected from the group consisting of cobalt, iron, and nickel.
[0033] Moreover, the ratio of silicon (Si) constituting the carrier 10 to the total of the metal elements (M) constituting the functional material 20 (atomic ratio Si / M) is preferably 10 to 1000, more preferably 50 to 200. If the ratio is more than 1000, the effect of the functional material may not be fully obtained, such as low activity. On the other hand, if the ratio is less than 10, the ratio of the functional material 20 becomes too large, and the strength of the carrier 10 tends to decrease. Note that the functional material 20 referred to here refers to fine particles held or supported inside the carrier 10, and does not include the functional material attached to the outer surface of the carrier 10.
[0034] [Functions of functional structures] As described above, the functional structure 1 includes a carrier 10 having a porous structure and at least one functional substance 20 present in the carrier. The functional structure 1 exerts the functionality of the functional substance 20 by contacting the functional substance 20 present in the carrier with a fluid. For example, when the functional structure 1 is used as a catalyst, the fluid that contacts the outer surface 10a of the functional structure 1 flows into the carrier 10 through the holes 11a formed in the outer surface 10a, is guided into the passage 11, moves through the passage 11, and exits the functional structure 1 through another hole 11a. In the path along which the fluid moves through the passage 11, the fluid comes into contact with the functional substance 20 present in the passage 11, causing a catalytic reaction by the functional substance 20 having catalytic activity. In addition, the functional structure 1 has a molecular sieve function due to the carrier having a porous structure.
[0035] First, the molecular sieving ability of the functional structure 1 will be described with reference to FIG. 2(a). As shown in FIG. 2(a), molecules 15a having a size equal to or smaller than the pore size of the hole 11a, in other words, equal to or smaller than the inner diameter of the passage 11, can penetrate into the carrier 10. On the other hand, molecules 15b having a size larger than the pore size of the hole 11a cannot penetrate into the carrier 10. In this way, when the fluid contains a plurality of types of compounds, the reaction of the compounds that cannot penetrate into the carrier 10 is restricted, and the compounds that can penetrate into the carrier 10 can be reacted.
[0036] Of the compounds produced in the carrier 10 by the reaction, only compounds composed of molecules having a size equal to or smaller than the pore size of the pores 11a can escape to the outside of the carrier 10 through the pores 11a and are obtained as reaction products. On the other hand, compounds that cannot escape to the outside of the carrier 10 through the pores 11a can be escaped to the outside of the carrier 10 if they are converted to compounds composed of molecules of a size that can escape to the outside of the carrier 10. In this way, by using the functional structure 1, a specific reaction product can be selectively obtained.
[0037] In the functional structure 1, as shown in FIG. 2(b), the functional substance 20 is enclosed in the expanded diameter portion 12 of the passage 11. The average particle diameter D of the functional substance C is the average inner diameter D of passage 11 F The inner diameter D of the expanded diameter portion 12 is larger than E If it is smaller than (D F <D C <D E ), small passages 13 are formed between the functional substances and the enlarged diameter portion 12. Then, as shown by the arrows in FIG. 2(b), the fluid that has entered the small passages 13 comes into contact with the functional substances. Since each functional substance is encapsulated in the enlarged diameter portion 12, movement within the carrier 10 is restricted. This prevents aggregation of the functional substances within the carrier 10. As a result, a large contact area between the functional substances and the fluid can be stably maintained.
[0038] In particular, by making the atomic ratio (Si / Al ratio) of silicon (Si) to aluminum (Al) in the carrier 10 2.0 or more, the production of zeolite-type crystals in the functional structure increases, making it possible to produce stronger zeolite-type compounds, thereby further improving the durability of the functional structure.
[0039] For example, when the functional structure 1 is used as a catalyst, when a molecule that has entered the passage 11 comes into contact with the functional material 20 having catalytic activity, the molecule (substance to be reformed) is reformed by a catalytic reaction. In the present invention, by using the functional structure 1 as a catalyst, for example, a mixed gas mainly composed of hydrogen and carbon monoxide can be used as a raw material to produce hydrocarbons (excluding CH4), preferably hydrocarbons having a carbon number of 2 to 20, more preferably olefins having a carbon number of 2 to 20 or aromatic hydrocarbons having a carbon number of 6 to 20. According to the functional structure 1 of the present invention, it is possible to produce hydrocarbons containing particularly low-grade (C2 to C4) hydrocarbons, and it is also possible to produce hydrocarbons containing more olefins than paraffins. This catalytic reaction is carried out at a high temperature of, for example, 180°C to 350°C, but since the functional material 20 is contained within the carrier 10, it is not easily affected by heating.
[0040] In particular, since the functional material 20 is present in the expanded diameter portion 12, the movement of the functional material 20 within the carrier 10 is further restricted, and the aggregation (sintering) of the functional materials 20 is further suppressed. As a result, the decrease in activity is further suppressed, and the life span of the functional structure 1 can be further extended.
[0041] [Method of manufacturing functional structures] FIG. 3 is a flowchart showing a method for manufacturing the functional structure 1 of FIG.
[0042] (Step S1: Preparation process) As shown in Fig. 3, first, a precursor material (A) for obtaining a support having a porous structure composed of a zeolite-type compound is prepared. The precursor material (A) is preferably a regular mesoporous substance, and can be appropriately selected depending on the type (composition) of the zeolite-type compound constituting the support of the functional structure.
[0043] Here, when the zeolite-type compound constituting the support of the functional structure is a silicate compound, the regular mesoporous material is preferably a compound consisting of a Si-O skeleton in which pores with a pore diameter of 1 to 50 nm are uniform in size and regularly developed in one dimension, two dimensions, or three dimensions. Such regular mesoporous materials can be obtained as various synthetic products depending on the synthesis conditions, and specific examples of synthetic products include SBA-1, SBA-15, SBA-16, KIT-6, FSM-16, MCM-41, etc., and among them, MCM-41 is preferable. The pore diameter of SBA-1 is 10 to 30 nm, the pore diameter of SBA-15 is 6 to 10 nm, the pore diameter of SBA-16 is 6 nm, the pore diameter of KIT-6 is 9 nm, the pore diameter of FSM-16 is 3 to 5 nm, and the pore diameter of MCM-41 is 1 to 10 nm. Examples of such regular mesoporous substances include mesoporous silica, mesoporous aluminosilicate, and mesoporous metallosilicate.
[0044] The precursor material (A) may be either a commercially available product or a synthetic product. The precursor material (A) can be synthesized by a known method for synthesizing regular mesoporous materials. For example, a mixed solution containing raw materials containing the constituent elements of the precursor material (A) and a template agent for defining the structure of the precursor material (A) is prepared, and the pH is adjusted as necessary to perform hydrothermal treatment (hydrothermal synthesis). Thereafter, the precipitate (product) obtained by the hydrothermal treatment is collected (for example, filtered), washed and dried as necessary, and further calcined to obtain the precursor material (A), which is a powdered regular mesoporous material. Here, the solvent for the mixed solution can be, for example, water, an organic solvent such as alcohol, or a mixed solvent thereof. The raw material is selected according to the type of carrier, and examples thereof include silica agents such as tetraethoxysilane (TEOS), fumed silica, and quartz sand. As the template agent, various surfactants, block copolymers, etc. can be used, and it is preferable to select according to the type of the compound of the regular mesoporous material. For example, when preparing MCM-41, a surfactant such as hexadecyltrimethylammonium bromide is suitable. The hydrothermal treatment can be carried out, for example, in a closed vessel under the treatment conditions of 80 to 800°C, 5 to 240 hours, and 0 to 2000 kPa. The calcination treatment can be carried out, for example, in air under the treatment conditions of 350 to 850°C, and 2 to 30 hours.
[0045] (Step S2: Impregnation process) Next, the prepared precursor material (A) is impregnated with a metal-containing solution containing a metal element to obtain a precursor material (B).
[0046] The metal-containing solution may be any solution containing a metal component (e.g., metal ion) corresponding to the metal element (M) constituting the functional material of the functional structure, and may be prepared, for example, by dissolving a metal salt containing the metal element (M) in a solvent. Examples of such metal salts include metal salts such as chlorides, hydroxides, oxides, sulfates, and nitrates, and among these, nitrates are preferred. Examples of the solvent that can be used include water, organic solvents such as alcohol, and mixtures of these.
[0047] The method of impregnating the precursor material (A) with the metal-containing solution is not particularly limited, but for example, it is preferable to add the metal-containing solution to the precursor material (A) in small amounts in multiple batches while stirring the powdered precursor material (A) before the firing step described below. In addition, from the viewpoint of making it easier for the metal-containing solution to penetrate into the pores of the precursor material (A), it is preferable to add a surfactant as an additive to the precursor material (A) before adding the metal-containing solution. Such an additive has the function of coating the outer surface of the precursor material (A), and is thought to suppress the adhesion of the metal-containing solution added thereafter to the outer surface of the precursor material (A), making it easier for the metal-containing solution to penetrate into the pores of the precursor material (A).
[0048] Examples of such additives include nonionic surfactants such as polyoxyethylene oleyl ether, polyoxyethylene alkyl ether, and polyoxyethylene alkyl phenyl ether. These surfactants have a large molecular size and cannot penetrate into the pores of the precursor material (A), so they do not adhere to the pores and do not prevent the metal-containing solution from penetrating into the pores. As a method for adding the nonionic surfactant, for example, it is preferable to add 50 to 500 mass% of the nonionic surfactant to the precursor material (A) before the firing step described below. If the amount of the nonionic surfactant added to the precursor material (A) is less than 50 mass%, the above-mentioned suppression effect is difficult to be exhibited, and if the nonionic surfactant is added to the precursor material (A) in excess of 500 mass%, the viscosity increases too much, which is not preferable. Therefore, the amount of the nonionic surfactant added to the precursor material (A) is set to a value within the above range.
[0049] In addition, it is preferable to appropriately adjust the amount of the metal-containing solution added to the precursor material (A) in consideration of the amount of the metal element (M) contained in the metal-containing solution impregnated into the precursor material (A) (i.e., the amount of the metal element (M) to be contained in the precursor material (B)). For example, before the firing step described below, it is preferable to adjust the amount of the metal-containing solution added to the precursor material (A) so that the ratio of silicon (Si) constituting the precursor material (A) to the metal element (M) contained in the metal-containing solution added to the precursor material (A) (atomic ratio Si / M) is 10 to 1000, and more preferably 50 to 200. For example, when a surfactant is added to the precursor material (A) as an additive before adding the metal-containing solution to the precursor material (A), the amount of the metal-containing solution added to the precursor material (A) is 50 to 200 in terms of atomic ratio Si / M, so that the metal element (M) contained in the functional material can be contained in an amount of 0.5 to 2.5 mass% relative to the functional structure. In the state of precursor material (B), the amount of metal element (M) present inside its pores is roughly proportional to the amount of metal-containing solution added to precursor material (A) under the same conditions such as the metal concentration of the metal-containing solution, the presence or absence of the above-mentioned additive, and other conditions such as temperature and pressure. In addition, the amount of metal element (M) present in precursor material (B) is proportional to the amount of metal element constituting the functional substance present in the support of the functional structure. Therefore, by controlling the amount of metal-containing solution added to precursor material (A) within the above range, the metal-containing solution can be sufficiently impregnated into the pores of precursor material (A), and thus the amount of functional substance present in the support of the functional structure can be adjusted.
[0050] After the precursor material (A) is impregnated with the metal-containing solution, a washing process may be performed as necessary. As the washing solution, water, an organic solvent such as alcohol, or a mixture of these can be used. In addition, after the precursor material (A) is impregnated with the metal-containing solution and washed as necessary, it is preferable to further perform a drying process. Examples of the drying process include natural drying for about one night, and high-temperature drying at 150°C or less. Note that if the calcination process described below is performed while a large amount of moisture contained in the metal-containing solution or the moisture of the washing solution remains in the precursor material (A), the skeleton structure of the precursor material (A) as a regular mesoporous material may be destroyed, so it is preferable to dry it thoroughly.
[0051] (Step S3: Firing process) Next, precursor material (A) for obtaining a porous support composed of a zeolite-type compound is impregnated with a metal-containing solution to obtain precursor material (B), which is then calcined to obtain precursor material (C).
[0052] The calcination treatment is preferably carried out in air at 350 to 850° C. for 2 to 30 hours, for example. By such a calcination treatment, the metal component impregnated in the pores of the ordered mesoporous material undergoes crystal growth, and a functional material is formed in the pores.
[0053] (Step S4: Hydrothermal treatment process) Next, a mixed solution is prepared by mixing the precursor material (C), a structure directing agent, and an aluminum source, and the precursor material (B) is calcined to obtain the precursor material (C), which is then subjected to a hydrothermal treatment to obtain a functional structure.
[0054] Structure directing agents are template agents for determining the skeletal structure of the framework (support) of a functional structure. They are organic structure directing agents (usually written as “organic structure directing agents” or “OSDA”) and OH -At least one of the inorganic structure directing agents having the above structure can be used. Among these, as the organic structure directing agent, for example, a surfactant can be used. The organic structure directing agent is preferably selected according to the skeletal structure of the support of the functional structure, and for example, surfactants such as tetramethylammonium bromide (TMABr), tetraethylammonium bromide (TEABr), tetrapropylammonium bromide (TPABr), and tetraethylammonium hydroxide (TEAOH) are suitable. Representative inorganic structure directing agents are hydroxides of alkali metals and alkaline earth metals, and for example, lithium hydroxide (LiOH), sodium hydroxide (NaOH), potassium hydroxide (KOH), rubidium hydroxide (Rb(OH)), calcium hydroxide (Ca(OH)2), and strontium hydroxide (Sr(OH)2) are suitable.
[0055] The aluminum source is a raw material for supplying aluminum contained in the support of the functional structure, and dissolves in water to supply Al ions. For example, NaAlO2 or Al(OH)3 is preferable.
[0056] The precursor material (C), the structure directing agent, and the aluminum source may be mixed during the hydrothermal treatment process, or may be mixed before the hydrothermal treatment process. The method for preparing the mixed solution is not particularly limited, and the precursor material (C), the structure directing agent, the aluminum source, and the solvent may be mixed at the same time, or the precursor material (C), the structure directing agent, and the aluminum source may be dispersed in a solvent in separate solutions, and then the respective dispersion solutions may be mixed. As the solvent, for example, water, an organic solvent such as alcohol, or a mixture of these may be used. It is also preferable to adjust the pH of the mixed solution using an acid or a base before performing the hydrothermal treatment.
[0057] The hydrothermal treatment can be carried out by a known method, and is preferably carried out in a sealed container under the treatment conditions of 80 to 800°C, 5 to 240 hours, and 0 to 2000 kPa. The hydrothermal treatment is also preferably carried out in a basic atmosphere. Although the reaction mechanism here is not necessarily clear, by carrying out hydrothermal treatment using the precursor material (C) as a raw material, the skeletal structure of the precursor material (C) as a regular mesoporous substance gradually collapses, but the position of the functional substance inside the pores of the precursor material (C) is roughly maintained, and a new skeletal structure (porous structure) as a skeletal body (support) of the functional structure is formed by the action of the structure-directing agent. At this time, aluminum is incorporated into the new skeletal structure. The functional structure thus obtained comprises a support having a porous structure and a functional substance (e.g., metal oxide fine particles) present in the support, and furthermore, the support has passages in which a plurality of pores are interconnected due to its porous structure, the atomic ratio (Si / Al ratio) of silicon (Si) to aluminum (Al) contained in the support 10 is 2.0 or more, and at least a part of the functional substance is retained in the passages of the support. Also, in the above-mentioned hydrothermal treatment step in this embodiment, a mixed solution is prepared by mixing the precursor material (C), a structure-directing agent, and an aluminum source, and the precursor material (C) is hydrothermally treated, but this is not limiting, and the precursor material (C) may be mixed with only the aluminum source without mixing the structure-directing agent, and the precursor material (C) may be hydrothermally treated.
[0058] The precipitate (functional structure) obtained after the hydrothermal treatment is preferably washed, dried and calcined as necessary after recovery (for example, filtration). As the washing solution, water, an organic solvent such as alcohol, or a mixture of these can be used. As the drying treatment, natural drying for about one night or high-temperature drying at 150°C or less can be used. If the precipitate is calcined while a large amount of moisture remains, the skeletal structure as a support for the functional structure may be broken, so it is preferable to dry it thoroughly. In addition, the calcination treatment can be performed, for example, in air at 350 to 850°C for 2 to 30 hours. By such a calcination treatment, the structure-directing agent attached to the functional structure is burned off. In addition, the functional structure can be used as it is without calcining the precipitate after recovery depending on the purpose of use. For example, when the environment in which the functional structure is used is a high-temperature environment in an oxidizing atmosphere, the structure-directing agent is burned off by exposing it to the use environment for a certain period of time, and the same functional structure as that obtained by calcination treatment can be obtained, so that it can be used as it is.
[0059] The above-described manufacturing method is an example in which the metal element (M) contained in the metal-containing solution to be impregnated into the precursor material (A) is a metal species that is difficult to oxidize (for example, Ru which is a noble metal).
[0060] (Step S5: Reduction process) On the other hand, when the metal element (M) contained in the metal-containing solution to be impregnated into the precursor material (A) contains a metal species (e.g., Fe, Co, Cu, etc.) that is easily oxidized and metal fine particles made of these metal species are used as the functional substance, it is preferable to perform a reduction treatment on the hydrothermally treated precursor material (C) after the hydrothermal treatment step. When the metal element (M) contained in the metal-containing solution is a metal species that is easily oxidized, the metal component is oxidized by the heat treatment in the steps (steps S3 to S4) after the impregnation treatment (step S2). Therefore, the support formed in the hydrothermal treatment step (step S4) contains metal oxide fine particles as a functional substance. Therefore, in order to obtain a functional structure in which a functional substance is contained in the support, it is desirable to perform a reduction treatment under a reducing gas atmosphere such as hydrogen gas after performing a calcination treatment on the precipitate recovered as necessary after the hydrothermal treatment. By performing the reduction treatment, the metal oxide fine particles contained in the support are reduced, and a functional substance consisting of metal fine particles corresponding to the metal elements constituting the metal oxide fine particles is formed. As a result, a functional structure having metal fine particles present as a functional substance in the carrier is obtained. At this time, the functionality provided by the functional substance can be adjusted by adjusting the degree of reduction in the reduction step. Such reduction treatment may be performed as necessary. For example, when the environment in which the functional structure is used can be at least temporarily a reducing atmosphere, the metal oxide fine particles are reduced by exposing the functional structure to a use environment including a reducing atmosphere for a certain period of time, and thus a functional structure similar to that obtained by reduction treatment is obtained, and it becomes possible to use the functional structure with the oxide fine particles present in the carrier as it is.
[0061] [Variations of functional structures] Fig. 4 is a schematic diagram showing a modified example of the functional structure 1 of Fig. 1. The functional structure 1 of Fig. 1 shows a case in which it includes a carrier 10 and a functional substance 20 present in the carrier 10, but is not limited to this configuration, and for example, as shown in Fig. 4, the functional structure 2 may further include another functional substance 30 held on the outer surface 10a of the carrier 10.
[0062] This functional material 30 is a material that exerts one or more functionalities at least during use. The functionality possessed by the other functional material 30 may be the same as or different from the functionality possessed by the functional material 20. In addition, when both of the functional materials 20 and 30 are materials having the same functionality, the material of the other functional material 30 may be the same as or different from the material of the functional material 20. According to this configuration, the content of the functional material held in the functional structure 2 can be increased, and the activity of the functional material can be further promoted.
[0063] In this case, the content of the functional material 20 present in the carrier 10 is preferably greater than the content of the other functional material 30 held on the outer surface 10a of the carrier 10. This allows the functionality of the functional material 20 held inside the carrier 10 to predominate, and the functionality of the functional material is stably exhibited.
[0064] [Application examples of functional structure 1] The functional structure 1 of the present invention can be used as a catalytic substance having a catalytic function, for example. In this case, a method for producing hydrocarbons may be provided in which the functional structure 1 is used as a catalyst to synthesize hydrocarbons from carbon monoxide and hydrogen. Such a catalyst includes a carrier 10 having a porous structure composed of a zeolite-type compound and at least one functional substance 20 present in the carrier 10, the carrier 10 having passages 11 communicating with each other, the atomic ratio (Si / Al ratio) of silicon (Si) to aluminum (Al) contained in the carrier 10 being 2.0 or more, and the functional substance 20 being present at least in the expanded diameter portion 12 of the passage 11 of the carrier 10. That is, the present invention provides a method for producing liquid hydrocarbons in which liquid hydrocarbons are synthesized from carbon monoxide and hydrogen using the above-mentioned functional structure. Furthermore, olefins can be preferentially produced by the FT synthesis reaction using this functional structure 1, as described above.
[0065] The raw material for carrying out such a method for producing hydrocarbons using the Fischer-Tropsch synthesis reaction is not particularly limited as long as it is a synthesis gas mainly composed of molecular hydrogen and carbon monoxide, but a synthesis gas having a hydrogen / carbon monoxide molar ratio of 1.5 to 2.5 is preferable, and a synthesis gas having the molar ratio of 1.8 to 2.2 is more preferable. The reaction conditions for the FT synthesis reaction are also not particularly limited, and the reaction can be carried out under known conditions. For example, the reaction temperature is preferably 200 to 500°C, and the pressure is preferably 0.1 to 3.0 MPa (absolute pressure).
[0066] The Fischer-Tropsch synthesis reaction can be carried out in a process known as a Fischer-Tropsch synthesis reaction process, for example, a fixed bed, a supercritical fixed bed, a slurry bed, a fluidized bed, etc. Preferred processes include a fixed bed, a supercritical fixed bed, and a slurry bed.
[0067] In addition, the present invention may provide a hydrocarbon production apparatus having the functional structure. Such a hydrocarbon production apparatus is not particularly limited as long as it can carry out a chemical reaction using the functional structure as a catalyst, and for example, a commonly used production apparatus such as an FT synthesis reaction apparatus or an FT synthesis reaction column can be used. By using the functional structure according to the present invention in such a hydrocarbon production apparatus, the production apparatus can also achieve the same effects as those described above.
[0068] The above describes the functional structure according to the embodiment of the present invention, the method for producing the same, the method for producing hydrocarbons using the functional structure, and the hydrocarbon production apparatus having the functional structure. However, the present invention is not limited to the above embodiment, and various modifications and changes are possible based on the technical concept of the present invention. EXAMPLES
[0069] (Examples 1 to 40) [Synthesis of precursor material (A)] A mixed aqueous solution was prepared by mixing a silica agent (tetraethoxysilane (TEOS), manufactured by Wako Pure Chemical Industries, Ltd.) with a surfactant as a template agent, and the pH was appropriately adjusted. The solution was subjected to hydrothermal treatment at 80 to 350°C for 100 hours in a sealed container. The resulting precipitate was then filtered, washed with water and ethanol, and calcined in air at 600°C for 24 hours to obtain powdered precursor material (A) with the type and pore size shown in Tables 1 and 3. The following surfactants were used according to the type of precursor material (A) ("Type of precursor material (A): Surfactant"). MCM-41: Hexadecyltrimethylammonium bromide (CTAB) (Wako Pure Chemical Industries, Ltd.)
[0070] [Preparation of precursor materials (B) and (C)] Next, metal-containing aqueous solutions were prepared by dissolving metal salts containing the metal elements (M) constituting the functional substances of the types shown in Tables 2 and 4 in water. The metal salts used were as follows, depending on the type of metal fine particles that are the functional substances ("metal fine particles: metal salts"). Co: Cobalt(II) nitrate hexahydrate (Wako Pure Chemical Industries, Ltd.) Ni: Nickel(II) nitrate hexahydrate (Wako Pure Chemical Industries, Ltd.) ·Fe: Iron(III) nitrate nonahydrate (manufactured by Wako Pure Chemical Industries, Ltd.) Ru: Ruthenium(III) chloride anhydrous (Tokyo Chemical Industry Co., Ltd.)
[0071] This precursor material (A) was pretreated by adding an aqueous solution of polyoxyethylene (15) oleyl ether (NIKKOL BO-15V, manufactured by Nikko Chemicals Co., Ltd.) as an additive (nonionic surfactant). Then, a metal-containing aqueous solution was added in small amounts in multiple batches to the precursor material (A), and the mixture was dried at room temperature (20°C ± 10°C) for 12 hours or more to obtain precursor material (B).
[0072] In addition, the amount of the metal-containing aqueous solution added to the precursor material (A) was adjusted so that the ratio of silicon (Si) constituting the precursor material (A) to the metal element (M) contained in the metal-containing aqueous solution (atomic number ratio Si / M) would be the value shown in Tables 1 and 3.
[0073] Next, the precursor material (B) impregnated with the metal-containing aqueous solution obtained as described above was calcined in air at 600° C. for 24 hours to obtain a precursor material (C).
[0074] The precursor material (C) obtained as described above was mixed with aluminum hydroxide (Al(OH)3, manufactured by Sigma Aldrich) as an aluminum source, and a structure directing agent shown in Tables 1 and 3 to prepare a mixed aqueous solution, which was then subjected to hydrothermal treatment in a sealed container at 80 to 350°C under the conditions of pH and time shown in Tables 1 and 3. The precipitate formed was then filtered, washed with water, dried at 100°C for 12 hours or more, and calcined in air at 600°C for 24 hours. The calcined product was then collected and reduced at 500°C for 60 minutes under a flow of hydrogen gas to obtain a functional structure having a support and metal fine particles shown in Tables 1 and 3 (Examples 1 to 40).
[0075] (Comparative Examples 1 to 3) In Comparative Examples 1 to 3, functional structures were obtained in the same manner as in Examples 1, 5 and 8, respectively, except that the atomic ratio of silicon (Si) to aluminum (Al) (Si / Al ratio) was set to 1.8.
[0076] Comparative Example 4 In Comparative Example 4, MFI type silicalite was mixed with cobalt oxide powder (II, III) (Sigma-Aldrich Japan LLC) having an average particle size of 50 nm or less, and hydrogen reduction treatment was performed in the same manner as in the Examples to obtain a functional structure in which cobalt fine particles were attached to the outer surface of the silicalite as a carrier. The MFI type silicalite was synthesized in the same manner as in Example 1, except for the step of adding metal.
[0077] Comparative Example 5 In Comparative Example 5, MFI type silicalite was synthesized in the same manner as in Comparative Example 4, except that the step of adhering cobalt fine particles was omitted.
[0078] [evaluation] Various characteristics of the functional structures of the above examples and the silicalite of the comparative example were evaluated under the conditions shown below.
[0079] [A] Cross-section observation Observation samples were prepared by a pulverization method for the functional structures of the above examples and the silicalite of the comparative example, and cross-sectional observation was performed using a transmission electron microscope (TEM) (TITAN G2, manufactured by FEI). As a result, it was confirmed that metal fine particles of cobalt, iron, nickel or ruthenium were present and held inside the carrier made of silicalite or zeolite in the functional structures of the above examples. On the other hand, in the silicalite of Comparative Example 4, metal fine particles of cobalt were only attached to the outer surface of the carrier, and were not present inside the carrier.
[0080] In addition, for the functional structures in the above examples in which the metal is iron (Fe) fine particles, cross sections were cut out by FIB (focused ion beam) processing, and cross-sectional elemental analysis was performed using SEM (SU8020, Hitachi High-Technologies Corporation) and EDX (X-Max, Horiba, Ltd.). As a result, Fe elements were detected from inside the support. From the results of the cross-sectional observations using the above TEM and SEM / EDX, it was confirmed that Fe fine particles existed inside the support.
[0081] [B] Average inner diameter of the carrier passages and average particle size of metal particles In the TEM image taken by the cross-sectional observation performed in the above evaluation [A], 500 passages of the carrier were randomly selected, the major axis and minor axis of each were measured, and the inner diameter of each was calculated from the average value (N=500). The average inner diameter was then calculated to obtain the average inner diameter D of the carrier passages. F It was decided.
[0082] In addition, to confirm the average particle size and dispersion state of the metal particles, analysis was performed using SAXS (small angle X-ray scattering). SAXS measurements were performed using the beamline BL19B2 at Spring-8. The obtained SAXS data was fitted to a spherical model using the Guinier approximation method, and the average particle size D of the metal particles was calculated. C was calculated. The particle size was measured for a functional structure having Fe fine particles as metal fine particles (functional substance). For comparison, commercially available Fe fine particles (manufactured by Wako) were observed and measured by SEM. The results are shown in Tables 2 and 4.
[0083] As a result, while the commercially available product contains iron particles of various sizes randomly in the particle size range of about 50 nm to 400 nm, the functional structures of each Example having metal particles with an average particle size of 1.5 nm to 1.6 nm showed, as a result of SAXS measurement, scattering peaks corresponding to the particle size values of each Example listed in Tables 2 and 4 within a particle size range of 10 nm or less. Furthermore, from the results of SAXS measurement and cross-sectional measurement by SEM / EDX, it was found that metal particles (Fe particles) with a particle size of 10 nm or less are present inside the carrier with a uniform particle size and in a highly dispersed state.
[0084] [C] Relationship between the amount of metal element (M) added to the precursor material (A) and the content of metal element (M) encapsulated as a functional substance inside the support constituting the functional structure When the precursor material (A) was impregnated with a metal-containing solution, the amount of metal element (M) added in the precursor material (A) was an atomic ratio of Si / M = 100, and a functional structure was produced in which metal fine particles were encapsulated inside the support as a functional substance. Thereafter, the amount of metal (mass%) encapsulated inside the support of each functional structure produced with the above-mentioned amount was measured.
[0085] The amount of metal was quantified using ICP (inductively coupled plasma) alone or a combination of ICP and XRF (X-ray fluorescence analysis). XRF (energy dispersive X-ray fluorescence analyzer "SEA1200VX", manufactured by SSI NanoTechnology) was performed under the conditions of a vacuum atmosphere and an acceleration voltage of 15 kV (using a Cr filter) or 50 kV (using a Pb filter). XRF is a method for calculating the amount of metal present from the fluorescence intensity, and quantitative values (converted to mass%) cannot be calculated using XRF alone. Therefore, the content of metal elements (M) and Si atoms in the functional structures to which metals were added at Si / M=100 were quantified using ICP analysis.
[0086] [D] Atomic ratio (Si / Al ratio) in the support The amounts of aluminum (Al) and silicon (Si) contained in the support were quantified using ICP (inductively coupled plasma).The atomic ratio (Si / Al ratio) was calculated from the amounts of aluminum (Al) and silicon (Si) measured.
[0087] [E] Performance evaluation The performance of the metal particles was evaluated for the functional structures of the above examples and the silicalite of the comparative example. The results are shown in Tables 2 and 4.
[0088] (1)Catalytic activity As an example of the performance of the metal fine particles encapsulated in the functional structure, the catalytic activity when the functional structure was used as a catalyst was evaluated under the following conditions. First, 70 mg of the functional structure was loaded into an atmospheric pressure flow reactor, hydrogen (8 ml / min) and carbon monoxide (4 ml / min) were supplied, and the pressure inside the reactor was adjusted to 0.1 MPa. The temperature was raised at 20°C / min in the range of 100-700°C, and then the temperature was maintained for 1 hour to perform Fischer-Tropsch synthesis. Here, a single microreactor (Frontier Labs, Rx-3050SR) was used as the atmospheric pressure flow reactor.
[0089] After the reaction was completed, the recovered product gas and product liquid were analyzed for components by gas chromatography mass spectrometry (GC / MS). Here, a TRACE 1310GC (manufactured by Thermo Fisher Scientific, Inc., detector: thermal conductivity detector) was used as the analyzer for the product gas and product liquid.
[0090] Furthermore, based on the results of the above component analysis, the products obtained by the FT synthesis reaction were confirmed. In this evaluation, the above operations were carried out at 250°C, 300°C, 350°C, and 400°C using the functional structures obtained in the examples and comparative examples, and the results were evaluated according to the following criteria.
[0091] Here, when the generation of hydrocarbons (excluding CH4, the same below) was confirmed at 250°C (i.e., when the reaction start temperature was 250°C or lower), the catalytic activity in the FT synthesis reaction was judged to be excellent and marked with a ◎; when the generation of hydrocarbons was confirmed at 300°C (i.e., when the reaction start temperature was higher than 250°C and lower than 300°C), the catalytic activity was judged to be good and marked with a ○; when the generation of hydrocarbons was confirmed at 350°C (i.e., when the reaction start temperature was higher than 300°C and lower than 350°C), the catalytic activity was judged to be poor and marked with a △; and when the generation of hydrocarbons was confirmed at 400°C (i.e., when the reaction start temperature was higher than 350°C and lower than 400°C) or when the FT synthesis reaction did not occur, the catalytic activity was judged to be very poor (unacceptable) and marked with an ×.
[0092] (2) Durability (lifespan) The durability was evaluated under the following conditions. First, the functional structure used in the above evaluation (1) was temporarily collected and then heated at 650° C. for 12 hours, and a functional structure after this heating was produced. Next, the FT synthesis reaction was carried out using the functional structure after heating in the same manner as in the above evaluation (1), and the components of the generated gas and the generated liquid were analyzed in the same manner as in the above evaluation (1).
[0093] Based on the obtained analysis results, the amount of hydrocarbons produced was determined using the same method as in the above evaluation (1). Furthermore, the extent to which the yield of hydrocarbons produced by the functional structure after heating was maintained was compared with the amount of hydrocarbons produced by the functional structure before heating. Specifically, the percentage (%) of the amount of hydrocarbons produced by the functional structure after heating (the amount produced in this evaluation (2)) relative to the amount of hydrocarbons produced by the functional structure before heating (the amount produced in the above evaluation (1)) was calculated.
[0094] In this example, when the amount of hydrocarbons generated by the functional structure after heating (the amount of generation determined in this evaluation (2)) was maintained at 80% or more compared to the amount of hydrocarbons generated by the functional structure before heating (the amount of generation determined in the above evaluation (1)), the durability (heat resistance) was judged to be excellent and marked with "◎", when it was maintained at 60% or more but less than 80%, the durability (heat resistance) was judged to be good and marked with "○", and when it fell to less than 60%, the durability (heat resistance) was judged to be poor (unacceptable) and marked with "X".
[0095] Similar performance evaluations were also carried out for Comparative Examples 1 to 5. Comparative Example 5 was the carrier itself and did not have metal fine particles. Therefore, in the above performance evaluation, instead of the functional structure, only the carrier of Comparative Example 5 was filled. The results are shown in Tables 2 and 4.
[0096] [Table 1]
[0097] [Table 2]
[0098] [Table 3]
[0099] [Table 4]
[0100] As is clear from Tables 1 to 4, the functional structures (Examples 1 to 40) in which it was confirmed by cross-sectional observation that metal fine particles, which are functional substances, were held inside the support, were found to exhibit excellent catalytic activity and also to be excellent in durability, particularly when used as catalysts for the FT synthesis reaction. Therefore, it is presumed that in the functional structures of Examples 1 to 40, aggregation of the functional substance held inside the support is less likely to occur.
[0101] In addition, the functional structure obtained in the above evaluation [C] was evaluated for the relationship between the amount of metal (mass%) encapsulated inside the carrier and the catalytic activity in the above evaluation (1). The evaluation method was the same as the evaluation method used in "(1) Catalytic activity" in the above [E] "Performance evaluation". As a result, it was found that in each example, when the amount of metal-containing solution added to the precursor material (A) was 100 in terms of the atomic ratio Si / M (the content of metal element (M) relative to the functional structure was 0.52 to 1.09 mass%), the catalytic activity was improved when used as a catalyst for the FT synthesis reaction, and the durability also tended to be improved.
[0102] Furthermore, the catalyst structure of the present invention was separately evaluated for the relationship between the amount of metal (mass%) encapsulated inside the carrier and the catalytic activity in the above evaluation (1). The evaluation method was the same as the evaluation method used in "(1) Catalytic activity" in the above [D] "Performance evaluation". As a result, it was found that the catalytic activity in the FT synthesis reaction tends to improve when the amount of metal-containing solution added to the precursor material (A) is 10 to 1000, converted into an atomic ratio Si / M, more preferably 50 to 200 (the content of metal element (M) relative to the catalyst structure is 0.5 to 2.5 mass%).
[0103] Furthermore, when comparing the catalytic activity of a functional structure in which metal fine particles containing Co are encapsulated with that of a functional structure in which metal fine particles containing Fe, Ni or Ru are encapsulated, the durability was evaluated as "◎" when the Si / Al ratio was 25 or more, regardless of whether Co, Fe, Ni or Ru was encapsulated as the metal fine particles. In particular, when Co was encapsulated as the metal fine particles, the durability was evaluated as "◎" even when the Si / Al ratio was 2 or more and less than 25. In contrast, when Fe, Ni or Ru was encapsulated as the metal fine particles, the durability was sometimes evaluated as "○" when the Si / Al ratio was 2 or more and less than 15. Representatively, the hydrocarbons (C2-C 20 ) and the GC / MS area was compared. As a result, the Co inclusion functional structure had a peak area approximately 1.4 times that of the Fe, Ni, and Ru inclusion functional structures. From these findings, it was found that Co is a more suitable inclusion metal species than Fe, Ni, or Ru.
[0104] On the other hand, in the functional structures of Comparative Examples 1 to 3, which had a small Si / Al ratio of 1.8, the zeolite compound did not crystallize, and the evaluation results for catalytic activity and durability were both "x." In addition, the functional structure of Comparative Example 4, in which metal fine particles were attached only to the outer surface of the support, had improved catalytic activity in the FT synthesis reaction compared to the support itself of Comparative Example 5, which did not have metal fine particles, but was inferior in both catalytic activity and durability to the functional structures of Examples 1 to 40.
[0105] From the above results, it can be inferred that the functional structures (Examples 1 to 40) exhibit excellent activity by suppressing aggregation of functional substances such as metal fine particles, and also have excellent durability. [Explanation of symbols]
[0106] 1 Functional structure 10. Carriers 10a outer surface 11 Passage 11a hole 12. Expanding section 20 Functional substances 30 Functional substances D C Average particle size D F Average inner diameter D E inner diameter
Claims
1. A porous support composed of a zeolite-type compound; A plurality of functional substances present in the carrier; Equipped with the functional substance is a metal fine particle containing one or more metals or alloys selected from the group consisting of cobalt (Co), iron (Fe), nickel (Ni) and ruthenium (Ru); The support contains aluminum (Al) and silicon (Si); The atomic ratio (Si / Al ratio) of silicon (Si) to aluminum (Al) contained in the carrier is 2.0 or more; the carrier has passages which communicate with each other, the passages having one-dimensional pores, two-dimensional pores, or three-dimensional pores of the framework structure of the zeolite-type compound, and an expanded portion different from any of the one-dimensional pores, the two-dimensional pores, or the three-dimensional pores; Among the plurality of functional substances, At least one functional substance is present in an inclusion state in at least the expanded diameter portion of the carrier, the average inner diameter of the passage is calculated from an average value of minor axes and major axes of pores constituting any one of the one-dimensional pores, the two-dimensional pores, and the three-dimensional pores; The average particle size of the functional substance is 0.08 nm to 30 nm; A catalyst material for a Fischer-Tropsch synthesis, characterized in that the average particle size of the functional material is greater than the average inner diameter of the passages and is equal to or smaller than the inner diameter of the expanded portion.
2. 2. The catalyst material for a Fischer-Tropsch synthesis according to claim 1, wherein the enlarged diameter portion connects a plurality of pores constituting any one of the one-dimensional pores, the two-dimensional pores, and the three-dimensional pores.
3. 3. The catalyst material for Fischer-Tropsch synthesis according to claim 1, wherein the metal element (M) of the functional material is contained in an amount of 0.5 to 2.5 mass % based on the catalyst material.
4. 4. The catalyst material for Fischer-Tropsch synthesis according to claim 1, wherein the functional material is fine metal oxide particles.
5. 5. The catalyst material for a Fischer-Tropsch synthesis according to claim 1, wherein the ratio of an average particle size of the functional material to an average inner diameter of the passages is 1.1 to 300.
6. The catalyst material for Fischer-Tropsch synthesis according to any one of claims 1 to 5, characterized in that the average inner diameter of the channels is between 0.1 nm and 1.5 nm.
7. 7. The Fischer-Tropsch synthesis catalyst material according to claim 1, further comprising at least one other functional material carried on the outer surface of the support.
8. 8. The catalyst material for Fischer-Tropsch synthesis according to claim 7, characterized in that the content of the at least one functional material present within the support is greater than the content of the at least one other functional material carried on the outer surface of the support.
9. The catalyst material for a Fischer-Tropsch synthesis according to any one of claims 1 to 8, characterized in that the zeolite type compound is a silicate compound.
10. A hydrocarbon production apparatus comprising the Fischer-Tropsch synthesis catalyst material according to any one of claims 1 to 9.
Citation Information
Patent Citations
Production of fischer-tropsch catalyst and use thereof in producing hydrocarbon
JP1984102440A
Manufacture of alumina extruded item
JP1992227847A
Hydrocarbon production catalyst, its production and production of hydrocarbon using same
JP2000070720A
Method for producing zeolite-encapsulated nanoparticles
JP2016523804A
Method for producing zeolite and zeolite-type
JP2016529190A